1998
DOI: 10.1121/1.422790
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic anisotropy in bovine cancellous bone

Abstract: This paper presents the experimental results on the acoustic anisotropy in bovine cancellous bone. The propagation of both fast and slow longitudinal waves in bovine cancellous bone was experimentally examined in relation to the structural anisotropy, or the trabecular arrangement. Propagation speeds of the fast and slow waves were measured as a function of the propagation angle to the trabecular alignment, and theoretically estimated by use of Biot's theory for an isotropic medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
165
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(182 citation statements)
references
References 12 publications
17
165
0
Order By: Relevance
“…4,14 Postmortem specimen studies have shown that ultrasound velocity is structure-related, as evidenced by its dependence on the measuring direction in bone cubes. 15,18,33,35,36 Furthermore, strong correlations between elastic moduli and ultimate strength, on the one hand, and ultrasound velocity, on the other, have been found in bovine 17,35,43 and human 5,12,15,17,36 trabecular bone samples. Recently, high-resolution microcomputed tomography (CT) reconstruction of trabecular bone was introduced.…”
Section: Introductionmentioning
confidence: 99%
“…4,14 Postmortem specimen studies have shown that ultrasound velocity is structure-related, as evidenced by its dependence on the measuring direction in bone cubes. 15,18,33,35,36 Furthermore, strong correlations between elastic moduli and ultimate strength, on the one hand, and ultrasound velocity, on the other, have been found in bovine 17,35,43 and human 5,12,15,17,36 trabecular bone samples. Recently, high-resolution microcomputed tomography (CT) reconstruction of trabecular bone was introduced.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10] In some experimental situations, the two waves are separated in the time-domain data, whereas in other circumstances the two waves substantially overlap and may appear as only a single wave. The degree to which the fast waves and slow waves overlap depends on a number of factors including porosity, structural anisotropy, ultrasonic path length, and the angle of insonification relative to the predominant trabecular orientation.…”
Section: Introductionmentioning
confidence: 99%
“…A reasonable agreement between Biot's theory and experiments has consistently been obtained when the phase velocity was considered, [11,12,19,21,23,24].…”
Section: Modelingmentioning
confidence: 76%
“…Its main advantage is the complete absence of ionizing radiation, while a disadvantage is the confounding influence of soft tissue. In last two decades many studies examined relevance of QUS in context of early detection of osteoporosis, [7,10,11,12,13,14,17,18,21,23]. Compared to reference x-ray absorptiometry techniques, which measure the amount of bone mineral content, it is regarded that ultrasound (being elastic wave) is sensitive not only to bone mass but also to structural and material properties of the material.…”
Section: Introductionmentioning
confidence: 99%